Artificial intelligence- image learning and its applications in neurooncology: a review - Malaika Javed; Mohammad Hamza Bajwa; Saqib Kamran Bakhshi (Journal of the Pakistan Medical Association, 2024)
Image learning involves using artificial intelligence (AI) to analyse radiological images. Various machine and deeplearning- based techniques have been employed to process images and extract relevant features. These can later be used to detect tumours early and predict their survival based on their grading and classification. Radiomics is now also used to predict genetic mutations and differentiate between tumour progression and treatment-related side effects. These were once completely dependent on invasive procedures like biopsy and histopathology. The use and feasibility of these techniques are now widely being explored in neurooncology to devise more accurate management plans and limit morbidity and mortality. Continue...